2021
DOI: 10.1155/2021/8865813
|View full text |Cite
|
Sign up to set email alerts
|

Emodin‐Induced Oxidative Inhibition of Mitochondrial Function Assists BiP/IRE1α/CHOP Signaling‐Mediated ER‐Related Apoptosis

Abstract: Cassiae Semen is a widely used herbal medicine and a popular edible variety in many dietary or health beverage. Emerging evidence disclosed that improper administration of Cassiae Semen could induce obvious liver injury, which is possibly attributed to emodin, one of the bioactive anthraquinone compounds in Cassiae Semen, which caused hepatotoxicity, but the underlying mechanisms are not completely understood. Hence, the present study firstly explored the possible role of oxidative stress-mediated mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Emodin-induced excessive ROS generation and redox imbalance promoted apoptosis, which was mainly associated with BiP/IRE1α/CHOP signaling-mediated ER stress and would be enhanced by oxidative stress-mediated mitochondrial dysfunction (Qiu et al, 2021) Pulmonary artery smooth muscle cells IRE1-XBP1 signaling way IRE1α-XBP1 pathway is involved in the process of hypoxia-induced pulmonary vascular remodeling; 4u8c could restrain hypoxia-induced cell proliferation and migration and reverse the hypoxia-induced apoptosis arrest, while quercetin excited excessive ERS and the IRE1 pathway in hypoxic PASMCs and promoted apoptosis (Cao et al, 2019) SH-SY5Y cell IRE1-MAMs signaling way Aβ peptides enhance cytotoxicity and mitochondrial damage in SH-SY5Y cells by targeting MAMs (Chu et al, 2021) Mouse liver cell IRE1-MAMs signaling way IRE1α deficiency resulted in marked alterations in mitochondrial physiology and energy metabolism under resting conditions (Carreras-Sureda et al, 2019) Abbreviations: IRE1, inositol-requiring enzyme 1; RIDD, regulated IRE1-dependent decay; ROS, reactive oxygen species.…”
Section: Ire1-related Signaling Pathwaysmentioning
confidence: 99%
“…Emodin-induced excessive ROS generation and redox imbalance promoted apoptosis, which was mainly associated with BiP/IRE1α/CHOP signaling-mediated ER stress and would be enhanced by oxidative stress-mediated mitochondrial dysfunction (Qiu et al, 2021) Pulmonary artery smooth muscle cells IRE1-XBP1 signaling way IRE1α-XBP1 pathway is involved in the process of hypoxia-induced pulmonary vascular remodeling; 4u8c could restrain hypoxia-induced cell proliferation and migration and reverse the hypoxia-induced apoptosis arrest, while quercetin excited excessive ERS and the IRE1 pathway in hypoxic PASMCs and promoted apoptosis (Cao et al, 2019) SH-SY5Y cell IRE1-MAMs signaling way Aβ peptides enhance cytotoxicity and mitochondrial damage in SH-SY5Y cells by targeting MAMs (Chu et al, 2021) Mouse liver cell IRE1-MAMs signaling way IRE1α deficiency resulted in marked alterations in mitochondrial physiology and energy metabolism under resting conditions (Carreras-Sureda et al, 2019) Abbreviations: IRE1, inositol-requiring enzyme 1; RIDD, regulated IRE1-dependent decay; ROS, reactive oxygen species.…”
Section: Ire1-related Signaling Pathwaysmentioning
confidence: 99%
“…It has been reported that emodin‐induced toxicity is correlated with glutathione (GSH) depletion and elevation of reactive oxygen species (ROS) (Huang et al, 2019; Qiu et al, 2021). Oxidative stress is defined by an imbalance between excessive ROS content and reduced activity of antioxidant mechanisms (Xie et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Given that the relationship between ER stress and DOX-induced cardiotoxicity has not been widely explored [ 28 , 29 ], we examined the role of an anti-ER stress chemical chaperone, tauroursodeoxycholic acid (TUDCA) in DOX-induced cardiomyopathy (Supplementary Fig. 14a ).…”
Section: Resultsmentioning
confidence: 99%